Bezpośrednie inwestycje zagraniczne a procesy transferu technologii - Wiśniewska, Joanna (Foreign Direct Investments and Technology Transfers, 2009)
Currently, the process of building the potential of competitiveness requires knowledge and technology investments. There are two different ways to do it: by developing R&D or by transferring technology. The processes of globalization and liberalization contribute to make FDI one of the important ways to get new technology at present. The main aim of the article is to present positive and negative effects of FDI in the context of technology transfer.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 879-886